Pengaruh penggunaan pembelajaran kooperatif tipe STAD berbantuan program Geometer’s Sketchpad terhadap kemampuan berpikir kreatif matematik siswa SMP - Satya Santika (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This study aimed to determine the increasements of mathematical creative thinking abilities of secondary school student after learning through cooperative learning Student Teams Achievement Divisions (STAD). This study used the quasi-experimental design with a control group, not equivalent. The study involved an experimental class given STAD cooperative learning assisted Geometer’s Sketchpad (GSP) and the control class was only given expository learning. Instruments used a set of mathematical creative thinking tests and questionnaires attitudes. The results showed that the students’ mathematical creative thinking ability can be improved through STAD cooperative learning STAD assisted Geometer’s Sketchpad.